Gait disorder rehabilitation using vision and non-vision based sensors: A systematic review - Asraf, Ali; Sundaraj, Kenneth, Prof. Madya Dr.; R. Badlishah, Ahmad, Prof. Dr.; Nizam, Ahamed; Anamul, Islam (Association of Basic Medical Sciences of Federation of Bosnia and Herzegovina, 2013)
Link to publisher's homepage at http://www.bjbms.org/publisher